First-time use of electronic patient-reported outcome measures in a cluster randomized trial: a qualitative study - Terese Solvoll Skåre; Tonje Lundeby; Jo Åsmund Lund; Marianne Jensen Hjermstad; May Helen Midtbust (Journal of Patient-Reported Outcomes)
Abstract Background Although there is clear evidence supporting the beneficial effects of regularly assessing patient-reported outcomes (PROs), the comprehensive integration of patient-reported outcome measures (PROMs) into routine cancer care remains limited. This study aimed to explore the facilitators and barriers encountered by principal investigators (PIs) (oncologists) and study nurses during the implementation of the Eir ePROM within a cluster randomized trial (c-RCT) in cancer outpatient clinics. Additionally, we sought to examine the influence of Eir on the working routines of the participants. Methods Individual semi-structured interviews and a focus group were conducted with nine oncologists and study nurses involved in the implementation of the ePROM tool Eir. Interviews elucidated their experiences of barriers and facilitators when implementing Eir through a cluster randomized trial. Data were analysed according to Framework Analysis, using both an inductive and deductive approach. The Consolidated Framework for Implementation Research (CFIR) was used in the deductive stages of analysis. Results Three overarching themes were identified from the data: (1) Willingness to invest; accepting that new eras come with a cost, (2) Management anchoring; changes start at the top, and (3) Creation of a cohesive framework; fostering collective comprehension. We found a notable disparity between oncologists and nurses in their willingness to invest time and effort in implementing the tool. While participants recognized the need to transform patient consultation methods to benefit from digital symptom management, opinions varied on whether the potential benefits justified the associated cost. Furthermore, the degree of management anchoring at various levels significantly impacted the implementation process. At the local level, it was seen as either a facilitator or a barrier, influencing the outcome of the implementation. Additionally, establishing a cohesive framework was crucial, as this fostered a collective understanding among those involved in the implementation. Conclusions Our study underscores the importance of considering the diverse perspectives of health care professionals and fostering interprofessional collaboration for the successful implementation of ePROMs in healthcare settings. Future research should explore strategies to bridge professional disparities and promote a shared understanding of the value provided by ePROMs.